1985
DOI: 10.1111/j.1365-2648.1985.tb00548.x
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of students with a predominantly arts educational background coping with the physiology component of a university nursing degree programme

Abstract: In this paper the authors discuss their experiences in admitting students with an arts 'A' (advanced) level General Certificate of Education background to an undergraduate nursing degree course. Firstly, the implications of students' different cognitive styles, both professionally and in teaching, are examined. Secondly, there is a description of an introductory course that has been used to assist students in the arts-science transition. Finally, the performance of 'arts' students, in a physiology course over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
(4 reference statements)
1
7
0
Order By: Relevance
“…An intensive summer study course for pre-college students just before starting their course has shown improvements in student performance (Rutishauser et al 1985). Preliminary analysis of the effect of workshop participation on subsequent student performance in A&P is also very encouraging in our case.…”
Section: Discussionsupporting
confidence: 55%
“…An intensive summer study course for pre-college students just before starting their course has shown improvements in student performance (Rutishauser et al 1985). Preliminary analysis of the effect of workshop participation on subsequent student performance in A&P is also very encouraging in our case.…”
Section: Discussionsupporting
confidence: 55%
“…1993, Nicoll & Butler 1996). Whilst difficulties in mastering a ‘hard science’ undoubtedly contribute to the anxiety (Rutishauser & Stephenson 1985), the strength of opinion expressed in this study suggests that the perceived necessity to understand the material for their practice is also a complicating factor.…”
Section: Discussionmentioning
confidence: 88%
“…"One way to achieve a suitable standard (in biological science) while not overloading is to establish the level of base knowledge required before starting the course." (McKee, 2002, p. 257) Making it compulsory to have a biological science background would prove unpopular, since it would limit the potential intake substantially (Payne, 1999), and equally, it is regarded as inappropriate to increase the amount of basic biological science taught at university (Rutishauser & Stephenson, 1985). Nicoll and Butler (1996) also found student resistance to the idea of introducing remedial lessons in biology, due to an unwillingness to demonstrate ignorance to the teacher.…”
Section: Discussionmentioning
confidence: 99%
“…They perceive biology as being an important part of the course, but few feel that they have an adequate level of knowledge (Courtenay, 1991). Unsurprisingly, previous biological experience has been found to influence performance in Biological Science (Rutishauser & Stephenson, 1985;Wharrad et al, 1994;Jordan et al, 1999, McKee, 2002. Rutishauer & Stephenson (1985) suggest that this may be due to lack of familiarity with scientific language, concepts or the nature of scientific thinking.…”
Section: Introductionmentioning
confidence: 99%